Symposium 6: E-tutoring “Contextualised Tutors’ Roles and Tutors’ Training”: Symposium Introduction - Denis, Brigitte (Proceedings of the International Conference on Networked Learning, 2004)
After a short introduction to the theme of this symposium on contextualised tutors’ roles and tutors’ training, we propose three papers. The first one deals with the definition of the e-tutor’s roles and competencies, the second illustrates the influence of the context and tutor roles in the tutor’s choice of media, and the third one describes three case studies of tutors training sessions.